EFFECTIVENESS OF MOXIFLOXACIN IN THE MANAGEMENT OF TUBERCULOUS MENINGITIS: A PILOT STUDY - Muhammad, Riaz; Ali, Zafar; Abdur Rahman Afridi, Muhammad; Asghar, Muhammad; Sebtain, Ali; Hussain, Sajid; Ahmad, Ejaz; Alam, Intekhab (Journal of Postgraduate Medical Institute, 2018)
Objective: To determine the effectiveness of moxifloxacin as fourth drug in the management of tuberculous meningitis (TBM). Methodology: This hospital based comparative clinical trial was done as pilot study from January 2016 to December 2017. The study was carried out on 43 patients with TBM. Moxifloxacin based regimen (group I) versus standard treat- ment for tuberculous meningitis (group II) were compared. Computer software, SPSS version 21.0, was used for data entry and analysis. Statis¬tical significance was considered at p value <0.05. Results: Out of 43 patients, there were 15 (34.9%) males and 28 (65.1%) females. Age of the patients ranged from 13 to 80 years (mean 31.418 ±18.62 years). Fe- ver, headache, vomiting and altered level of consciousness was present in 38 (88.4%); neck stiffness in 39 (90.69%) and neurological deficit was present in 18 (41.9%) patients. Leptomeningeal enhancement was the most frequent radio- logical finding found in 13 (30.2%) patients. Overall Improvement occured in 38 (88.37%) of patients. In group I, 21/22 (95.45%) patients and in group II, 17/21 (80.95%) patients improved, (p value 0. 158). Till 3rd day of commencement of treatment, 11/21 (52.38%) patients recovered in group I while 02/17 (11.76%) patients recovered in group II. Conclusion: Moxifloxacin based regimen was associated with an early recovery (within 03 days of commencement of treatment) in a significant number of patients with TBM.